EVALUATION OF SIMULATION INTRAVENOUS ADMIXTURE TRAINING FOR STUDENTS ENROLLED IN AN INTRODUCTORY PHARMACY PRACTICE EXPERIENCE - Jusczak, Patricia; Ma, Carolyn; Wongwiwatthananukit, Supakit (Interprofessional Journal of Health Sciences, 2023)
The purpose of this study was to evaluate the effect of the addition of simulation intravenous admixture laboratory training sessions for the first year Doctor of Pharmacy (PharmD) students prior to participating in the Introductory Pharmacy Practice Experience (IPPE) at the hospital. Students completed six hours of structured training sessions in the principles of aseptic technique and intravenous (IV) admixture preparation, including simulation of hospital procedures. At the end of the IPPE hospital rotation, students completed the survey related to their perceptions towards the simulation training of IV admixture/hospital experience prior to the IPPE, the IV simulation sessions, and the degree to which the sessions helped to increase their confidence in performing activities encountered during hospital rotation. Students reported very positively that the IV training sessions benefited them in multiple areas. The simulation training should become an effective approach to integrate into the coursework for the IPPE hospital experiential rotation.